Perbandingan Jenis Bank Syariah : Bank Umum, BPRS, dan Unit Usaha Syariah - M. Ihsan Zaki Nasution; Syanda Rabiatul Adawiyah (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This study aims to compare the types of Islamic banks in Indonesia, namely Islamic Commercial Banks (BUS), Islamic People’s Financing Banks (BPRS), and Islamic Business Units (UUS). This study uses a quantitative method taken from 15 relevant journals, with a systematic data analysis approach. The focus of this study covers several important aspects, such as finance, operational efficiency, and the risks faced by each type of Islamic bank. The results of the study show that UUS has higher efficiency compared to BUS and BPRS, which can be seen from better financial ratios. Meanwhile, BPRS shows a better level of profit despite having a smaller scale of operation. These findings provide important insights for the development of the Islamic banking industry in Indonesia, and can be a reference for stakeholders in formulating more effective policies. Therefore, this study not only contributes to the literature academy but also provides practical applications for the development of the Islamic banking sector in the country.